2005
DOI: 10.1128/jvi.79.3.1480-1486.2005
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Use of CXCR4 by R5X4 Human Immunodeficiency Virus Type 1 Isolates for Infection of Primary Lymphocytes

Abstract: Coreceptor specificity of human immunodeficiency virus type 1 (HIV-1) strains is generally defined in vitro in cell lines expressing CCR5 or CXCR4, but lymphocytes and macrophages are the principal targets in vivo. CCR5-using (R5) variants dominate early in infection, but strains that use CXCR4 emerge later in a substantial minority of subjects. Many or most CXCR4-using variants can use both CXCR4 and CCR5 (R5X4), but the pathways that are actually used to cause infection in primary cells and in vivo are unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 39 publications
6
67
0
Order By: Relevance
“…2A), use CXCR4 exclusively for entry into PBMC. These results are consistent with the results of recent studies that demonstrated preferential use of CXCR4 by R5X4 HIV-1 isolates for infection of primary T lymphocytes (51). The data also indicate that DR-17 and C2-16 Envs, which are dual-tropic for T lymphocytes and macrophages ( Fig.…”
Section: Vol 80 2006supporting
confidence: 82%
See 1 more Smart Citation
“…2A), use CXCR4 exclusively for entry into PBMC. These results are consistent with the results of recent studies that demonstrated preferential use of CXCR4 by R5X4 HIV-1 isolates for infection of primary T lymphocytes (51). The data also indicate that DR-17 and C2-16 Envs, which are dual-tropic for T lymphocytes and macrophages ( Fig.…”
Section: Vol 80 2006supporting
confidence: 82%
“…2A). Consistent with previous studies, ADA and 89.6 Envs entered PBMC and MDM, whereas HXB2 Env entered PBMC but not MDM (18,19,34,42,43,(49)(50)(51). All C2 and DR Envs entered PBMC, but only C2-16 and DR-17 Envs entered MDM.…”
Section: Vol 80 2006supporting
confidence: 77%
“…The lysates were then incubated at 60°C for 2 h and 98°C for 15 min. For each reaction, 1 l of DNA lysate was transferred to a MicroAmp fast optical 96-well reaction plate with a barcode (Applied Biosystems) containing 12.5 l TaqMan Universal PCR Master Mix (Applied Biosystems), 9 l of sterile water (Fisher Scientific), and 1.5 l of the primer/probe sets recognizing an early HIV replication product (the first strong stop or long terminal repeat [LTR]) or the cellular GAPDH (glyceraldehyde 3-phosphate dehydrogenase) gene (61). RealTime PCR was then performed using the Applied Biosystems 7500 Fast RealTime PCR System.…”
Section: Methodsmentioning
confidence: 99%
“…While many HIV-1 strains can use either CCR5 or CXCR4 (R5X4 viruses) to infect cell lines, the efficiency with which a given virus uses each coreceptor for infection can vary widely and does not always predict the mechanism of entry into human T cells or macrophages (18). Thus, some R5X4 viruses use only CXCR4 to infect certain primary cells, others use only CCR5, and some viruses use both coreceptors to infect multiple cell types (16,17,26,36,(59)(60)(61). The use of specific and potent coreceptor antagonists can be utilized to prevent entry via one coreceptor, revealing the efficiency with which the alternative coreceptor can support virus infection.…”
mentioning
confidence: 99%
“…SHIV-89.6P therefore behaves in PBMCs as if it were an X4 virus (12). However, SHIV-89.6P can use either CCR5 or CXCR4 to enter indicator cell lines, and some dual-tropic viruses that use only CXCR4 to enter T cells can also use CCR5 for replication in macrophages (17,18). Our unpublished studies suggest that CMPD-167 or AMD3465 can each inhibit SHIV-89.6P vaginal transmission to macaques, albeit inconsistently.…”
mentioning
confidence: 99%